2015
DOI: 10.1002/rrq.103
|View full text |Cite
|
Sign up to set email alerts
|

Practices and Commitments of Test-centric Literacy Instruction: Lessons From a Testing Transition

Abstract: During the 2011–2012 academic year, Texas public schools began administering the State of Texas Assessments of Academic Readiness (STAAR) in grades 3–8, replacing the old testing system, the Texas Assessment of Knowledge and Skills (TAKS). The TAKS–STAAR transition is a unique contextual backdrop for studying the role of state‐mandated reading and writing tests in the assessment and learning environments of elementary and middle schools. In this study, drawing on extensive interview data, we detail the test‐ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 77 publications
0
21
0
Order By: Relevance
“…As Davis and Willson (2015) found in their study about the impact of standardized testing on teaching, "Instead of instructional…”
Section: Limitationsmentioning
confidence: 98%
See 3 more Smart Citations
“…As Davis and Willson (2015) found in their study about the impact of standardized testing on teaching, "Instead of instructional…”
Section: Limitationsmentioning
confidence: 98%
“…The study also found that teachers felt they were incorporating less instruction in narrative genres than they had prior to CCSS, and that they believed the neglect of narrative and imaginative writing assignments was diminishing student engagement . Davis and Willson (2015) also found dissatisfaction regarding pressure to enact testpreparatory practices among teachers interviewed about the implementation of CCSS tests in Texas. Given the powerful influence of these tests on multiple stakeholders, research regarding how CCSS is influencing assessment design is needed.…”
Section: Consequences Of High-stakes Examsmentioning
confidence: 99%
See 2 more Smart Citations
“…PreK-12 classroom teachers must be competent teaching practitioners who are equipped with well-defined knowledge about literacy development and know how to apply this expertise with impactful pedagogical practices among diverse learners (ILA & National Council of Teachers of English [NCTE], 2017). In the present accountabilityfocused era, PreK-12 classroom teachers must also be learner-centered practitioners who prioritize research-based and responsive approaches to literacy instruction over test-centric teaching practices (Au & Valencia, 2010;Davis & Willson, 2015). Ultimately, PreK-12 classroom teachers must be trained as literacy leaders who engage in lifelong learning, reflect upon their practices, collaborate with other practitioners, and advocate for powerful literacy teaching and learning (ILA, 2018a).…”
Section: Introductionmentioning
confidence: 99%